FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU HIDUP BERSIH DAN SEHAT PADA PEKERJA BAGIAN PRODUKSI PT. COCA COLA AMATIL INDONESIA CENTRALJAVA - Annisa Restiyani; Kusyogo Cahyo; Laksmono Widagdo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Based on a report by the policlinic health services of PT. Coca Cola Amatil Indonesia Central Java, the prevalence of contagious diseases in 2015 was recorded 976 cases of respiratory disorders and 317 cases of indigestion. Until August 2016, it was recorded 270 cases of respiratory disorders and 73 cases of indigestion. These cases mostly happened on worker in the production section. This research aims to analyze factors relating to clean and healthy living behavior of workers in the production division at PT. Coca cola Amatil Indonesia Central Java.Method used in this research is quantitative method with cross sectional approach and simple random sampling technique. Data was collected by interview using questionnaire to 70 respondents from workers in the production division of PT. Coca Cola Amatil Indonesia Central Java and analyzed using chi square. The result of this research shows most of the respondents are in the age of over 40 years (50%), a senior high school graduate (74%), and has joined the company for over 15 years (62.9%). The chi square test showed that the duration of joining the company (p=0.045), infrastructures and facilities (p=0.0001), support from the head officer (p=0.048), and support from health officer in the workplace (p=0.003) are related to the clean and healthy living behavior in workplace. While the variables of age, education, knowledge of PHBS, attitude of PHBS, access of information, availablity of rules, and support from co-workers are not significantly related to clean and healthy living behavior on worker in the production section at PT. Coca Cola Amatil Indonesia Central Java.